The spatial distribution characteristics of Nb–Ta of mafic rocks in subduction zones - Li Weiwei (De Gruyter, 2021)
High field-strength elements have been regarded as one of the most important discriminations in subduction zone magma. However, the spatial distribution of Nb and Ta in subduction zone-related rocks has been rarely studied; it is still unclear whether there is a quantitative relationship between the Nb–Ta concentrations and their subduction distance. In this paper, the Nb–Ta concentrations of mafic rocks in arc tectonic systems were calculated from a statistical perspective based on the combined geophysical model and geochemical database. The results showed a typical spatial distribution pattern. The threshold value of Nb (12.20 ppm) and Ta (0.796 ppm) in arc settings was estimated by a cumulative distribution function, which can be used to determine whether the rock is generated in arc tectonic environment. A probability density function of Nb–Ta contents and related subduction distance has been obtained using kernel function estimation. The Nb–Ta concentrations are exponentially correlated with the subduction distance (<700 km), while the Nb/Ta ratios keep in the range of 12–19. We proposed that the subduction depth, along with the degree of partial melting, and possible crustal contamination might be responsible for the Nb–Ta variation correlation with subduction distances.